Clinical and microbiological features and outcomes of mucormycosis in critically ill patients. (August 2021) - Rothe, Kathrin; Braitsch, Krischan; Okrojek, Rainer; Heim, Markus; Rasch, Sebastian; Verbeek, Mareike; Schmid, Roland M.; Busch, Dirk H.; Lahmer, Tobias
Highlights: Mucormycosis is associated with high mortality rates in critically ill patients. Diagnostic strategies are needed. Aggressive antifungal therapy is essential for intensive care patients with mucormycosis. ABSTRACT: Introduction: Mucormycosis is a rare invasive fungal infection with high mortality in patients with severe underlying predisposing factors causing immunosuppression. The exact incidence of mucormycosis and the optimal therapeutic approach is difficult to determine, especially in severe cases, due to the rarity of the disease. The new second-generation triazole isavuconazole provides an alternative treatment option which may represent a potential benefit in severe cases. Materials and methods: A retrospective case series was conducted of patients with a positive laboratory culture for Mucorales and consistent clinical findings who required intensive care treatment. Patient characteristics including demographics, comorbidities, microbiological analysis, specific antifungal therapy and clinical outcome were analysed. Results: Fifteen critically ill patients with Mucorales detected between 2016 and 2019 were included in this study; the crude mortality rate was 100%. At the time of diagnosis of mucormycosis, 80% of subjects had relevant medical immunosuppression and 53.3% of subjects had neutropenia. Manifestation of mucormycosis was pulmonary in 53.3% of subjects, rhino-orbital in 20% of subjects and disseminated in 26.7% of subjects. Notably, 40% of all patients had received antifungal prophylaxis prior to mucormycosis, mainly with posaconazole due to underlying haematological malignancy, thus possibly representing break-through infections. Antifungal therapy for invasive mucormycosis was administered in 80% of subjects for a median duration of 16 days. Conclusion: In this retrospective cohort analysis of intensive care patients, the prognosis of mucormycosis was extremely poor. An aggressive strategy for diagnosis and treatment is essential for intensive care patients with mucormycosis. There is a need for further research to determine if combination therapy in higher dosages or prompt surgery is beneficial in severe critically ill patients.